2013
DOI: 10.3146/ps13-4.1
|View full text |Cite
|
Sign up to set email alerts
|

Glufosinate Application Timing and Rate Affect Peanut Yield

Abstract: Field studies were conducted at 13 locations across the US peanut belt during 2010-2012 to evaluate peanut response to postemergence applications of glufosinate. Glufosinate was applied at 0, 41, 82, 164, 328 and 656 g ai/ha 30, 60, and 90 days after planting (DAP). There was a significant interaction for peanut yield between application time and glufosinate rate; peanut yield data were regressed on rate of glufosinate and fit to a log-logistic dose response curve by application timing. At 30 DAP, peanut yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
5
12
0
Order By: Relevance
“…Lassiter et al (2007) reported that peanut exposed to 280 g ae ha À1 of glyphosate decreased pod yield by approximately 20% at several locations. Prostko et al 2013 showed that glufosinate at 82 g ai ha À1 caused similar yield reduction at multiple sites. In both studies, yield loss surpassed 50% when herbicide rate was above 560 g ha À1 .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Lassiter et al (2007) reported that peanut exposed to 280 g ae ha À1 of glyphosate decreased pod yield by approximately 20% at several locations. Prostko et al 2013 showed that glufosinate at 82 g ai ha À1 caused similar yield reduction at multiple sites. In both studies, yield loss surpassed 50% when herbicide rate was above 560 g ha À1 .…”
mentioning
confidence: 94%
“…In the southeastern United States, peanut production occurs in close proximity to or in rotation with cotton (Gossypium hirsutum L.) and soybean [Glycine max (L.) Merr.] (Lassiter et al 2007;Prostko et al 2013). New cotton and soybean transgenic varieties with traits conferring resistance to the synthetic auxin herbicides 2,4-D and dicamba (2,4-DR and DR, respectively) have been developed (Behrens et al 2007;Johnson et al 2010;Wright et al 2010) and are expected to be quickly adopted by growers who will use these traits to control glyphosate-resistant (GR) weed species (Craigmyle et al 2013;Robinson et al 2012;Spaunhorst and Bradley 2013).…”
mentioning
confidence: 99%
“…Peanut is regularly grown near cotton (Gossypium hirsutum L.) and soybean [Glycine max (L.) Merr.] across the southeast (Lassiter et al, 2007;Prostko et al, 2011;Prostko et al, 2013). A large percentage of cotton and soybean cultivars have herbicide resistance technology to assist in weed management, and the increased use of glyphosate and glufosinate herbicides throughout the growing season increased the occurrence of accidental injury to peanut crops (Grey and Prostko, 2010;Johnson et al, 2012a;Lassiter et al, 2007).…”
mentioning
confidence: 99%
“…Peanut is commonly grown in the proximity of cotton and soybean across the southeast (Lassiter et al, 2007;Prostko et al, 2011;Prostko et al, 2013). Herbicide resistance technology is used in most cotton and soybean cultivars for weed management solutions, and the increased use of glyphosate and glufosinate herbicides throughout the growing season increased the occurrence of accidental injury to sensitive crops like peanut (Grey and Prostko, 2010;Johnson et al, 2012a;Lassiter et al, 2007).…”
mentioning
confidence: 99%